A case of pulmonary foreign body granuloma formation after transcatheter arterial chemoembolization for hepatocellular carcinoma. Issue 11 (13th October 2021) - Murata, Saori; Nakamura, Morio; Sasada, Shinji; Kirita, Keisuke; Ishioka, Kota; Takahashi, Saeko; Usui, Yusuke; Tsuchiya, Yumi; Seki, Reishi
Key message: We experienced a case of pulmonary foreign body granuloma diagnosed by bronchoscopy in a patient with multiple lung lesions after transcatheter arterial chemoembolization (TACE) for hepatocellular carcinoma. We speculate that the lesions may be caused by transarterial migration of the materials used for TACE. Abstract : We present a case of pulmonary foreign body granuloma diagnosed by bronchoscopy in a patient with multiple lung lesions after transcatheter arterial chemoembolization for hepatocellular carcinoma.